Congenital membranous cataract surgery in an 11-week-old child with persistent fetal vasculature: a case report - Lubiński, Wojciech; Kirkiewicz, Marta; Modrzejewska, Monika; Soszka-Przepiera, Ewelina (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
The report presents the surgical management of membranous cataract associated with persistent fetal vasculature. A routine ophthalmological examination in a 3-month-old infant revealed total cataract in the left eye. Persistent hyperplastic vitreous body was visualized on B-scan ultra-sound. Under general anesthesia, the cataract was removed through a 1.2 mm corneal microincision, combined with the removal of the fibro-vascular retrolenticular membrane and excision of the persistent vitreous artery, anterior vitrectomy, and iridectomy. Early diagnosis and surgi-cal management allow further diagnosis and rehabilitation of the eye with persistent fetal vasculature.